The Role of Meta-Cognitive, Dysfunctional Cognition and Early Maladaptive Schemas on Obsessive Compulsive Disorder - Fatemeh Rezaei (Journal of Global Pharma Technology, 2018)
This study aimed to examine the mediating role of meta-cognitive and dysfunctional cognition in the relationship between early maladaptive schemas and obsessive-compulsive disorder (OCD). The study participants consisted of 600 staff of Khuzestan Steel Company (KSC). They filled out the following questionnaires: Obsessive-Compulsive Inventory-Revised (OCI-R, Obsessive Beliefs Questionnaire-44 (OBQ-44), Dysfunctional Attitude Scale (DAS), Young's 90-item Early Maladaptive Schemas Questionnaire, Meta-Cognitive Belief Inventory and Negative Automatic Thoughts Questionnaire (NATQ). The results indicated that the proposed model has an acceptable fit (RMSEA=0.078). According to this model, early maladaptive schemas directly and indirectly predicted the OCD (β=0.93, P<0.0001) through metacognitive beliefs (CI= 0.18-0.09) and dysfunctional cognition (CI= 0.31-0.14). It was also revealed that dysfunctional cognition is mediating between early maladaptive schemas and the OCD (CI= 1.14-0.13). This study illustrated that the early maladaptive schemas restrain the surface cognitive processing. Therefore, it is recommended that the early maladaptive schemas, metacognition, and dysfunctional cognition are attended to treat the OCD.Keywords: Early Maladaptive Schemas, Meta-cognitive, Dysfunctional Cognition, Obsessive-Compulsive Disorder.